Exploring beyond the conjunctural rhetoric: Sociocultural drivers for the 'cassava crisis' in Côte d'Ivoire - Aubin Jacob Mobio; Gilbert Fokou; Solange Aka; Kouadio Benal Kouassi; Katharina Sophia Kreppel; Kouakou Philipps Kouakou; Nogbou Andecthi Aubin Amanzou; Daouda Dao; Bassirou Bonfoh (Agricultural and Food Economics, 2021)
Despite considerable improvement of food security in low- and middle-income countries over the last decades, food shortages remain persistent in sub-Saharan Africa. The driving forces are often related not only to climate change and other environmental hazards but also to socioeconomic and political factors. In Africa, food security has also assumed a strong urban dimension, raising new issues of physical and financial access to food. However, beyond the conjunctural rhetoric around unregulated food policies, social unrest, socio-economic difficulties, and environmental stresses, an emphasis should be put on socio-cultural aspects of food security. This would be possible through an analysis of "connectivities" between various stages and actors, i.e., food exchange practices between various socioecological spaces, and governance coordination in food security strategies. Based on a study on cassava shortage in Cote d'Ivoire in 2015-2016, this paper explores sociocultural factors associated with food shortage in urban settings. Findings from a qualitative research approach comprising key-informant interviews and focus group discussion with various stakeholders in the cassava value chain revealed that food shortage cannot always be explained by supply/demand narratives. The study shows that cassava supply mechanisms in the Abidjan area are not sustainable as the main producers of cassava for sale are migrant workers employed in rubber plantations and whose stability in the region depends on prices of this cash crop on the international market. Regions at the vicinity of Abidjan are supplying the city with cassava but the offer does not meet the requirements of cassava-based food processors who need specific types of the product. Moreover, strategies from the municipal and government authorities to circumvent the shortage often face resistance of populations if local norms and values are not considered. In food strategies, sociocultural dynamics should be considered alongside the complex socioeconomic and environmental factors shaping the social geography of food supply in African cities.
Keywords: 330; Cassava crisis; Food shortage; Migrant producers; Sociocultural driver; Connectivity; Abidjan; Côte d'Ivoire